2012
DOI: 10.1002/bip.22093
|View full text |Cite
|
Sign up to set email alerts
|

Application of principal component analysis to determine the key structural features contributing to iron superoxide dismutase thermostability

Abstract: Iron superoxide dismutase (Fe-SOD) is predominantly found in bacteria and mitochondria. The thermal stability of Fe-SOD from different sources can vary dramatically. We have studied the influence of structural parameters on Fe-SOD thermostability by principal component analysis (PCA). The results show that an increased α-helical and turn content, an increased α-helix and loop length, an increase in the number of main-main chains and charged-uncharged hydrogen bonds, a decrease in the 3(10) -helix content, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 96 publications
0
8
0
Order By: Relevance
“…However, its applications are limited by SOD leakage and desorption. The subunits that constitute Fe- and Mn-SOD dimers or tetramers share a wide range of sequence similarities (which can be as low as 25.4 %) but possess virtually identical protein folds and active-site geometries (Jackson and Brunold 2004 ; Wintjens et al 2004 ; Ding et al 2012 ). SODA NG2215 and SODA Ss share highly similar backbones, conserved metal-binding residues and nearly identical tetrameric structures (Additional file 1 : Fig S1).…”
Section: Discussionmentioning
confidence: 99%
“…However, its applications are limited by SOD leakage and desorption. The subunits that constitute Fe- and Mn-SOD dimers or tetramers share a wide range of sequence similarities (which can be as low as 25.4 %) but possess virtually identical protein folds and active-site geometries (Jackson and Brunold 2004 ; Wintjens et al 2004 ; Ding et al 2012 ). SODA NG2215 and SODA Ss share highly similar backbones, conserved metal-binding residues and nearly identical tetrameric structures (Additional file 1 : Fig S1).…”
Section: Discussionmentioning
confidence: 99%
“…It was believed that α-helical content, α-helix length, and even the salt bridges formed by the charged residues, such as Arg and Glu, are important factors for Fe-SOD thermostability. In contrast, the β-strand is negatively correlated via a principal component analysis of five thermophilic SODs and six mesophilic counterparts 25 . Superimposing this model with SOD structures (1MA1, 3AK1, 3EVK, 1B06, and 1WB8) revealed that these tertiary structures are well conserved, especially the regions around the ion binding site.…”
Section: Discussionmentioning
confidence: 99%
“…Recent efforts to improve the thermal resistance of SODs through chemical modification, gene recombination, and simulated SOD compounds have achieved considerable success 23 24 . Bioinformatic methods have also been used to guide the bioengineering process 25 . Nevertheless, the generality of these methods is limited because the determinants of protein thermostability are numerous.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It can be considered as a rule that natural thermostable and especially hyperthermostable proteins are characterized by a larger number of charged (titratable) amino acids. This feature has been reported for a large number of individual cases and summarized in comparative studies . Although the physical principles of the stabilizing effect of electrostatic interactions at high temperature are known, the picture will be incomplete without considering the internal motion (flexibility) inherent to the protein molecule.…”
Section: Electrostatic Stability Contribution Of Ion Pairs Ionic Netmentioning
confidence: 95%